ISOLATION AND CHARACTERIZATION OF CHEMICAL CONSTITUENTS FROM Chrysophyllum albidum G. DON-HOLL. STEM-BARK EXTRACTS AND THEIR ANTIOXIDANT AND ANTIBACTERIAL PROPERTIES - Idowu, T. O.; Ogundaini, Abiodun Oguntuga; Adesanya, S. A.; Onawunmi, G. O.; Osungunna, M. O.; Obuotor, E. M.; Abegaz, B. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The plant, Chrysophyllum albidum is indigenous to Nigeria and its stem-bark has found relevance in folkloric medicine for infections and oxidative stress linked diseases medicaments. The study targets to isolate the chemical constituents accountable for the antioxidant and antibacterial actions of the plant stem-bark to substantiate some of its ethnomedicinal uses. Materials and Methods: Stem-bark extract of Chrysophyllum albidum was obtained from 80 % ethanol was partitioned in sequence with ethyl acetate (EtOAc) and n-butanol. The solvent fractions and isolated compounds were verified for antioxidant chattels utilizing 2-2-diphenyl-1-picrylhydrazyl. Antibacterial actions were also assessed by agency of agar-diffusion and broth micro dilution methods. EtOAc fraction was on many occasions chromatographed on silica and Sephadex LH-20 column to afford four compounds and their chemical structures were proven with the employment of NMR (1D and 2D) and MS. Results: Chromatographic fractionation of EtOAc fraction with the premier antioxidant and antimicrobial activities afforded stigmasterol (1), epicatechin (2), epigallocatechin (3) and procyanidin B5 (4). Procyanidin B5 isolated for the first time from Chrysophyllum genus proven the supreme antioxidant activity with IC50 values of 8.8 µM and 11.20 µM in DPPH and nitric oxide assays respectively and equally established the ultmost inhibitory activity against Escherichia coli (MIC 156.25 μg/mL), Staphylococcus aureus (MIC 156.25 μg/mL), Pseudomonas aeruginosa (MIC 625 μg/mL) and Bacillus subtilis (MIC 156.25 μg/mL). Conclusion: The antibacterial and antioxidant activities of epicatechin, epigallocatechin and procyanidin B5 isolated from Chrysophyllum albidum stem-bark substantiate the folkloric uses